2019
DOI: 10.5603/gp.2019.0120
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal hospice care in the opinion of nurses and midwives

Abstract: Objectives: Perinatal medicine is a relatively new, dynamically developing branch of medicine. Its main purpose is taking care of a woman in the pre-conception period, pregnancy and delivery, as well as taking care of a newborn baby. The main aim of the study was to assess the state of knowledge and opinion on hospice perinatal care of professionally active nurses and midwives. Material and methods: An original and anonymous questionnaire containing 30 questions was used for the study. 572 nurses and midwives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Also, Chan et al (2005) show that many professionals consider their understanding of the bereavement situation to be merely instinctive, and in relation to this, Ravaldi et al (2018) reveal that many of their actions were based on personal beliefs and guided only by compassion; in their study, 75% of nurses/midwives had never attended a course on perinatal bereavement care (Ravaldi et al, 2018), a widespread pattern (Chan et al, 2008, 2010) that, for Jonas‐Simpson et al (2013), could be solved by providing bereavement education in nursing schools or even at work. Our results about training deficits are in line with previous research that has shown a great variability in the bereavement care offered to families, probably resulting from the absence of guidelines on care, in both NPC/PH settings (Cerratti et al, 2020; Dahò, 2021) and mixed settings (NPC‐PH/Obstetrics and Gynaecology [OAG]; Fernández‐Alcántara et al, 2020; Gruszka et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, Chan et al (2005) show that many professionals consider their understanding of the bereavement situation to be merely instinctive, and in relation to this, Ravaldi et al (2018) reveal that many of their actions were based on personal beliefs and guided only by compassion; in their study, 75% of nurses/midwives had never attended a course on perinatal bereavement care (Ravaldi et al, 2018), a widespread pattern (Chan et al, 2008, 2010) that, for Jonas‐Simpson et al (2013), could be solved by providing bereavement education in nursing schools or even at work. Our results about training deficits are in line with previous research that has shown a great variability in the bereavement care offered to families, probably resulting from the absence of guidelines on care, in both NPC/PH settings (Cerratti et al, 2020; Dahò, 2021) and mixed settings (NPC‐PH/Obstetrics and Gynaecology [OAG]; Fernández‐Alcántara et al, 2020; Gruszka et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to studies such as André et al (2020), Gruszka et al (2019) and Shen et al (2022), Chan et al (2003) showed that the majority of nurses (90.9%) felt positive attitudes and feelings when they provided bereavement care, while Ravaldi et al (2018) reported that a large proportion of nurses (76.8%) felt that they were providing adequate support for the family. In fact, our literature review reveals that high satisfaction usually emerges when nurses/midwives: (a) develop a holistic approach to care, (b) have the ability to provide women and families with opportunities to be with the newborn and (c) can develop postpartum care (Fenwick et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Cortezzo et al [14] also revealed that more than one-third of the physicians who participated in their study did not have sufficient time to complete the BPs with parents, and that some of the physicians felt uncomfortable creating the BPs with the family. A lack of education and training of healthcare providers on caring for critically ill babies was also reported [22,23]. Documenting women's hopes expressed in BPs is essential for healthcare providers to ably facilitate women to facilitate women's care.…”
mentioning
confidence: 99%